Pressure effect on structural, electronic optical and thermodynamic properties of cubic AlxIn1-xP: a first-principles study. (1st February 2020) - Bencherif, B.; Abdiche, A.; Moussa, R.; Khenata, R.; Wang, Xiaotian
ABSTRACT: First-principles total energy calculations have been performed using the full potential linearised augmented plane wave (FP-LAPW) method as implemented in the WIEN2k code based on the density functional theory (DFT) to investigate the Al-doping effects on the structural, electronic and optical properties of Alx In1-x P ternary alloys in the zinc-blende (ZB) phase. Different approximations of exchange-correlations energy were used such as the local density approximation (LDA), the generalised gradient approximation within parameterisation of Perdew–Burke–Ernzerhof (PBE-GGA), and the Wu-Cohen (WC-GGA). In addition, we have calculated the band structures with high accuracy using the Tran-Blaha modified Becke–Johnson (TB-mBJ) approach. The pressure dependence of the electronic and optical properties of binary AlP, InP compounds and their related ternary alloys Alx In1-x P were also investigated under hydrostatic pressure for ( P  = 0.0, 5.0, 10.0, 15.0, 20.0, 25.0 GPa), where it is found that InP compound change from direct to indirect band gap for P  ≥ 9.16 GPa. Furthermore, we have calculated the thermodynamic properties of InP and AlP binary compounds as well as the Alx In1-x P solid solutions, where the quasi-harmonic Debye model has been employed to predict the pressure and temperature dependent Gibbs free energy, heat capacity, Debye temperature and entropy. GRAPHICAL ABSTRACT: